Exploring Tension Fabric Structure and Material- A Review of The Bigo Arena and Denver International Airport - Merve Sumeyye Taha; Abdulmajeed Mamhusseini Asmaa; Shino Abdullah (Eurasian journal of science and engineering (Online), 2024)
The fact that tension fabric structures are light and durable, as well as visually pleasing, has become a reason for preference, especially in contemporary architecture. In this article, in addition to a comprehensive evaluation of stretchable fabric structures, two important stretchable fabric systems, Bigo Arena and Denver International Airport, are used as case studies. By comparing these two case studies, this study pays attention to the differences and properties of the materials while also emphasizing the advantages of the tensile fabric structure. It aims to give ideas to researchers working on this subject by researching the materials and techniques used during construction and examining the possibilities, such as their impact on progress and sustainability in architecture. The Denver International Airport and Bigo Arena serve as prime examples of how membrane systems may be used successfully in architectural projects. While PTFE-coated glass fiber material is preferred in the construction of lightweight structures, it also provides the opportunity to capture solar radiation. Through the projects examined in this research, it is emphasized that fiberglass material coated with PTFE is an example of how interior spaces can be more useful by creating both aesthetic and well-lit spaces. In summary, the case studies demonstrate the successful application of membrane frameworks to achieve functional and aesthetically acceptable goals in architecture.